Effect of matrix saturation magnetization on particle capture in high gradient magnetic separation. (1st August 2019) - Wang, Yuhua; Xue, Zixing; Zheng, Xiayu; Lu, Dongfang; Li, Si; Li, Xudong
Highlights: Numerical simulation of magnetic field around matrices with different Ms . Calculation of particle capture cross section with extended capture models. Particle capture cross section area increases with Ms when matrices are saturated. Matrices with relatively larger λ and higher Ms enhance particle capture. Abstract: The performance of high gradient magnetic separation (HGMS) system is influenced by many configuration and operation parameters. We have previously investigated the effect of these influencing parameters such as applied magnetic induction, fluid velocity, matrices size and shape etc. We derived extended particle capture models for cylinder matrices in HGMS, considering both the case that matrices were unsaturated and saturated by applied induction. A convenient method relating to matrix saturation magnetization Ms for judging magnetization state of matrices was proposed. Matrix saturation magnetization Ms is a very important parameter in HGMS and is worthy of being investigated. In this paper, effect of matrix saturation magnetization on particle capture performance in HGMS is studied through numerical simulation and theoretical calculation. The induced magnetic field and particle capture cross section of SUS 430, pure iron and cobalt steel matrices are equivalent and increase with saturation magnetization Ms when the matrices are unsaturated and saturated by applied induction, respectively. Matrices with larger aspect ratio λ have wider applied induction range within which higher saturation magnetization Ms will present superiority. Adopting matrices with relatively large aspect ratio and high saturation magnetization can enhance recovery of fine weakly magnetic minerals in vertical ring high gradient magnetic separator. This is also applicable to horizontal ring magnetic separator in which grooved plates (prone to saturation) are adopted.